Music Education Within the Concept of Integrated Arts Education and Its Impact on Social and Emotional Skills of Students - Vereshchahina-Biliavska, Olena; Solovei, Viktor; Burska, Olena; Hrinchenko, Tetiana; Moskvichova, Yuliia (Pedagogika, 2024)
The purpose of the study is to determine how communicative skills and emotional intelligence are cultivated in students under the impact of arts on the example of music education. The research involves comparing social and emotional competences of undergraduates and postgraduates with the help of standardized psychological tests and interviews. The article proves that integrated arts education transforms students into emotionally and socially competent individuals.